Om postkolonialisme, migrasjonsprosesser og hybride identiteter. En lesning av Eva Scheers Vi bygger i sand (1948) - Brovold, Madelen Marie (Folia Scandinavica Posnaniensia, 2019)
This article examines what one might call migration literary features in the Jewish Norwegian author Eva Scheer’s novel Vi bygger i sand (1948). I will investigate themes and sections that in different ways emphasize the migration experience of the characters within the novel. The focal point of the analysis is the migration experience in itself, what it means to be forced to move from one country to another and having to learn how to live in a different country and community, perceived identity and identity issues, prejudices, anti-Semitism and the fear of persecution. Because of this chosen focal point, I will use postcolonial theory in my reading of the novel, emphasizing Homi K. Bhabha’s concepts of mimicry and hybridity. What does it mean to belong to a nation? Is it possible to become Norwegian while keeping parts of your homeland’s identity? With the altered migration pattern of recent decades, such issues make the novel relevant even today.